Klinični pomen novih metod (količina hemoglobina v retikulocitih in hipokromni eritrociti) za oceno pomanjkanja železa v telesu - Preložnik-Zupan, Irena (Zdravniški vestnik, 2004)
Background. Classical iron deficiency does not represent a particular diagnostic challenge for the clinicians. However, in several more complicated clinical conditions, classical biochemical indices such as serum iron, transferrin saturation and ferritin may not be informative enough to reflect transient iron-deficient states and functional iron de ficiency. It is definedas an imbalance between iron needs of the erythroid marrow and the ironsupply. Two hematological parameters, the proportions of hypochromic red cells (hypoE) and reticulocyte hemoglobin content (CHr), have major value in this setting. Conclusions. CHr and hypoFprovide a useful new approach to the diagnosi,s of iron-deficient states. CHr is an early marker of functional irondeficiency, as reticulocytes exist in the circulation for only 1-2 days. Because erythrocytes have a lifespan about 120 days, the hypoE is able to provide information over a several month period and is a late indicator of iron-restricted erythropoiesis. With these new parameters identification of iron deficiency could be improved in some clinical conditions such as erythropoietin therapy, anemia of chronic disease, iron deficiency of early childhood and in the illicit use of erythropoietin for blood doping of competitive athletes. We have already introduced both new methods in clinical practice with cooperation between Department of hematology and Institut for Clinical Chemistry and Biochemistry.
Keywords: Anemia, Hypochromic; Anemia, Iron-Deficiency; anemija; Anemija hipokromna; Anemija, železo, pomanjkanje; Eritropoietin rekombinantni; Erythropoietin, Recombinant; hemoglobin; Hemoglobinometrija; Hemoglobinometry; Iron; kri; Metabolism; Reticulocyte Count; Reticulocytes; Retikulociti; Retikulociti, štetje; therapy; zdravljenje; Železo